Vitamin D in autistic children and healthy controls - Bičíková, M; Máčová, L; Ostatníková, D; Hanzlíková, L (Physiological research, 2019)
Insufficient levels of vitamin D have been demonstrated by many authors as a risk factor for autistic patients, however, the causality has not been reliably elucidated. In the present study, levels of calcidiol were determined in group of autistic children and compared with age matched healthy children as controls. Suboptimal levels of calcidiol in more than 60 % of both autistic patients as well as of control group were found. No significant differences in vitamin D between autistic children and healthy controls were observed.
Keywords: biologické markery; kalcifediol; mužské pohlaví; poruchy autistického spektra; Autism Spectrum Disorder; Calcifediol; Biomarkers; Healthy Volunteers; lidé; vitamin D; Child; Humans; dítě; zdraví dobrovolníci pro lékařské studie; Male; předškolní dítě; Vitamin D; Child, Preschool